Implication of sphingolipid metabolism gene dysregulation and cardiac sphingosine-1-phosphate accumulation in heart failure. (14th October 2021) - Perez Carrillo, L; Sanchez Lazaro, I; Martinez Dolz, L; Portoles, M; Rosello-Lleti, E; Tarazon, E
Abstract: Introduction and purpose: Abnormal levels of bioactive sphingolipids have been linked to disturbances in a variety of biological functions of several diseases, including cardiovascular diseases. However, changes in sphingolipid metabolism associated with progressive human heart failure (HF) have not been described, and S1P levels in HF tissues have not been evaluated. Methods: We investigated changes in the transcriptome of human heart tissues using RNA sequencing technologies. We collected 26 left ventricular (LV) tissue samples from HF patients undergoing heart transplantation and 10 samples from healthy controls (CNT), and subjected these to mRNA-seq; and an additional 42 HF tissues and 8 CNT for the ncRNA-seq. In addition, we determined the bioactive sphingolipid levels in these tissues (HF, n=36; CNT, n=5) using ELISA. Results: Most major changes were observed in expression of genes belonging to de novo (SPTSSA, −1.46±0.25; SPTSSB, −2.46±0.21; SPTLC1, −1.52±0.37; SPTLC3, −1.60±0.36; PPARA, −1.19±0.17; CERS1, 1.98±1.05; p<0.05), and salvage pathways (ACER1, −1.70±0.28; ACER3, 1.19±0.26; SGPP1, −1.49±0.24; p<0.05; SGPP2, −2.83±0.28; S1PR3, −1.78±0.28, p<0.01). Furthermore, we observed that the tight regulation of these genes by their miRNA regulatory partners is largely dysregulated in HF. In addition, we verified that two key bioactive sphingolipids, ceramide (307±218 vs. 81±79 ng/mL, p<0.01) and S1P (1908±625 vs. 963±489 ng/mL; p<0.05) accumulate in cardiac tissue during HF, with the ceramide/S1P ratio increasing by as much as 57% in HF patients. Interestingly, CERS1 expression was linked to changes in LV mass (r=0.797, p<0.0001), LV end-systolic (LVESD, r=0.561, p<0.05) and end-diastolic diameters (LVEDD, r=0.601, p<0.01), while S1P levels were inversely correlated with these parameters (LVESD, r=−0.552; LVEDD, r=−0.541; p<0.05). Conclusions: In this study, we outline the changes in the key components of the sphingolipid metabolism, mainly in the de novo and the salvage pathways, which lead to cardiac ceramide and S1P accumulation and the increase in the ceramide/S1P ratios in HF patients. Gene modulation targeting ceramide and/or S1P levels may be beneficial in the treatment of these patients. Specifically, CERS1 is linked to cardiac remodeling, making it a good candidate for the treatment of patients with HF. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institute of Health Carlos IIIEuropean Regional Development Fund (ERDF)